If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 20 = 80 Reorder the terms: 20 + m = 80 Solving 20 + m = 80 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + m = 80 + -20 Combine like terms: 20 + -20 = 0 0 + m = 80 + -20 m = 80 + -20 Combine like terms: 80 + -20 = 60 m = 60 Simplifying m = 60
| Y^4=400 | | 7x^6=12 | | -2/4/7 | | 2r-36=6r-12 | | 0=4k^2-15k+20 | | -35/-0.875 | | 3(k+1)+2k=13 | | 2x^4=120 | | -7x^2-24x-9=0 | | 3m+4=12 | | p14=-20 | | m+80=140 | | t(25)=0.07(25)^3/2 | | 6x=-18y-12 | | 5x-3=6x-2x | | 0y-5(1+y)=3(2y-2)-20 | | F(x)=(t-1)(t+3) | | 2t-7-52=11 | | 3x-5=7x-49 | | 42=-6g | | 4/9y-3 | | e^5x+8=13 | | -3(1+4.5r)=-17.5 | | 1x^2+4x-6=0 | | v/7=-13 | | 7.4r+9-2r=25.2 | | 7x+7=3-5z | | m=4m+11 | | X+(-56)=-7 | | -12=12m | | 0.25(20)+0.7x=0.6(20+x) | | 5x-4-x=2x-1 |